Prior expectations of leadership programme attendees’ and their subsequent reflections on completion of the programme - Jooste, K (South African Journal of Higher Education, 2016)
The article describes the reflection on personal expectations of nursing academics prior to commencement of a leadership programme and their subsequent reflections on completion of this introduction to the leadership programme. The programme aimed at developing the participants as leaders in conjunction with development of the culture of research in a school of nursing at a university in the Western Cape, South Africa. A qualitative, exploratory and descriptive design was used. A total sample of 8 nurse academics at a higher education institution took part and narratives were written in July 2012. The results indicated active participation and involvement, development of skills and knowledge, a balance between programme and personal goals, a sense of confidence amongst attendees, creating structure for growth, and critical thinking. The implication of this study was that a leadership research team has been established with clear underlying assumptions of transformative leadership in research driven by self-leadership.